Cyber-Indigeneity: Urban Indigenous Identity on Facebook - Lumby, Bronwyn (The Australian Journal of Indigenous Education, 2010)
Abstract This paper addresses understandings and theorising of identity in cyberspace. In particular, it focuses on the construction, maintenance and performance of urban Indigenous identities on the contemporary internet social space, Facebook.